Establishment of a Mouse Submandibular Salivary Gland Organ Culture. Issue 9 (7th September 2022) - Sakai, Manabu; Sakai, Takayoshi
Abstract: The salivary glands produce saliva and are important in maintaining oral health. Saliva keeps the mouth moist, cleanses the oral cavity, aids digestion, and has antibacterial properties. Saliva also helps in swallowing and speech. Investigating the development of the salivary glands is thus relevant in the context of both health and disease. Various cell culture methods have been used to study salivary gland development, including culturing cells in two dimensions (2D). Under physiological conditions, cells constantly interact with other cells and the extracellular matrix, which controls complex biological functions such as cell migration and apoptosis, and can modulate gene expression. Since many of these functions are not accurately represented or reproduced in 2D culture, the results of in vitro experiments using such culture methods are often not reflected in vivo . The use of 3D cultures, such as organ cultures, has helped address this issue and has emerged as a model that better reflects the in vivo physiological environment. Here, we describe a protocol for establishing submandibular salivary gland organ culture that is more concise and simpler than previous methods and includes the separation and dissection of the salivary glands. We also describe the use of environmental stress (hypoxic stimulation) and inhibitors (U0126, LY294002, and rapamycin) to elucidate signaling pathways involved in salivary gland development. This protocol can provide researchers with a simpler and more robust method of salivary gland organ culture, enabling analysis of organ‐based signaling pathways to advance developmental biology research. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Submandibular salivary gland organ culture Basic Protocol 2 : Analysis of salivary gland development in the presence of hypoxia and signaling pathway inhibitors Basic Protocol 3 : Western blotting using submandibular salivary gland organ culture